Recognition Of Islamic Boarding Schools-An Analysis of Law No. 18 Of 2019 - Husnul Yamil; Ahyar; Saparudin (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This research analyzes Indonesia’s Law Number 18 of 2019 on pesantren (Islamic boarding schools) as a form of state recognition within the politics of Islamic education. Utilizing a combined library research and content analysis and then policy study approach informed by contemporary literature, the study traces the genealogy of pesantren recognition in the national education system and critically examines its implications for institutional status, curriculum development, and resource allocation. Findings reveal that while the law provides formal legitimacy and expands access to state resources, it also introduces bureaucratic standards that may constrain the epistemological autonomy of pesantren. Varied responses among pesantren reflect ongoing negotiations between traditions of religious scholarship and demands of modernization. The research concludes that the effectiveness of legal recognition largely depends on the pesantren’s internal capacities to negotiate with state mechanisms and on implementation frameworks that respect institutional diversity. Policy recommendations include differentiated implementation strategies, curricular autonomy safeguards, strengthened human resource capacity, and participatory accountability models.